Bidirectional two-sample Mendelian randomization study of atrial fibrillation and breast cancer - Fan Ding; Fan Ding; Chen Chen; Yuling Wang; Yuling Wang; Tingting Zhu; Linke Jiao; Linke Jiao; Zihuan Shen; Zihuan Shen; Zhiwei Zhang; Lifei Lv; et al. (Frontiers in Cardiovascular Medicine)
BackgroundObservational studies have shown an association between Breast Cancer (BC) and Atrial Fibrillation (AF). However, due to confounding factors and reverse causality, the causal role between BC and AF remains unclear. In this study, bidirectional two-sample Mendelian randomization (MR) combined with meta-analysis was used to evaluate the causal association between BC and AF.MethodsBased on the Genome-Wide Association Studies (GWAS) summary data sets, the Inverse variance weighted (IVW) method was used as the main method, the weighted median method and MR-Egger method were used for Bidirectional Two-Sample Mendelian Randomization, and the Egger intercept test was used to detect horizontal pleiotropy. Heterogeneity was tested by Cochran's Q test, and sensitivity analysis was performed by “leave-one-out”. GWAS data for AF and BC were obtained from three separate databases (FinnGen, UKBiobank, GWAScatalog) for European individuals. Finally, meta-analysis was performed on the MR Analysis results from different databases.ResultsThe pooled IVW results showed no evidence of an effect of BC on the risk of AF (IVW: OR = 0.9994; 95% CI = 0.9967–1.0022). There was also no evidence of an effect of AF on BC risk (IVW: OR = 0.9970; 95% CI = 0.9154–1.0859).ConclusionThe results of the Bidirectional Two-Sample Mendelian Randomization study show that there is no causal relationship between BC and AF.